2021
DOI: 10.1101/2021.11.23.469646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local synchronization of cilia and tissue-scale cilia alignment are sufficient for global metachronal waves

Abstract: Motile cilia are hair-like cell extensions present in multiple organs of the body. How cilia coordinate their regular beat in multiciliated epithelia to efficiently displace fluids remains elusive. Here, we propose the zebrafish nose as an accessible model system to study ciliary dynamics, due to its conserved properties with other ciliated tissues and its high availability for non-invasive imaging. We reveal that cilia are locally synchronized, and that the size of local synchronization domains increases with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…To analyze ciliary beating frequency (CBF), we suggest two methods using a MATLAB script or an ImageJ/Fiji plugin (FreQ). The experimenters can choose their method of choice because both methods adapt a similar Fourier-based principle to analyze CBF ( Figure 4 A) ( Haward et al., 2021 ; Reiten et al., 2017 ; Ringers et al., 2021 ). However, we recommend the experimenters to always use the same method for their analysis, since there are slight differences in their output results, as indicated in the limitations section and in Figure 10 .…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…To analyze ciliary beating frequency (CBF), we suggest two methods using a MATLAB script or an ImageJ/Fiji plugin (FreQ). The experimenters can choose their method of choice because both methods adapt a similar Fourier-based principle to analyze CBF ( Figure 4 A) ( Haward et al., 2021 ; Reiten et al., 2017 ; Ringers et al., 2021 ). However, we recommend the experimenters to always use the same method for their analysis, since there are slight differences in their output results, as indicated in the limitations section and in Figure 10 .…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…Hence it is crucial to make sure that there are no drifts in x and y axis prior to the analysis. If you observe drift in x,y, you may try to correct those with an alignment code prior to the CBF analysis described earlier ( Reiten et al., 2017 ; Ringers et al., 2021 ). However, it is important that you check manually, frame by frame that, after correction, the sample is no longer drifting in the image.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also reported that the increasing cilia length provides an increased directional flow rate, and a smaller cilia length with a random beating pattern results in increased flow mixing [ 54 ]. Besides, the way ciliary beating is synchronized and how synchronization modulates fluid pumping remain poorly understood [ 55 ]. Notably, metachronal waves, which refer to cilia beating with a time delay between neighbors [ 1 , 56 ], have been commonly described for multi-ciliated cells and are suggested to improve fluid pumping [ 55 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%